JavaScript and the Netflix User Interface. - LIU, ALEX (Communications of the ACM, 2014)
The article discusses the redevelopment of desktop application in JavaScript, the official programming language of the Web. Topics discussed include the support for the language by consumer hardware devices through the integration of a Web browser application, devices' support of Web views as part of the operating system user interface (UI), Netflix's development of highly complex UIs, testing on the Netflix website which adds features to enhance the control experience and asynchronous module definition (AMD) libraries.